Memorandum of understanding between Universiti Teknologi MARA and Politeknik Negeri Bandung / Fakulti Pengurusan Hotel & Pelancongan - Universiti Teknologi MARA, Fakulti Pengurusan Hotel & Pelancongan (Universiti Teknologi MARA (UiTM), 2020)
Memorandum of understanding on friendship and cooperation, promotion of mutual understanding, academic, cultural and scientific thought and personnel exchange.